MULTI-OBJECTIVE PARAMETRIC OPTIMISATION OF MASKED STEREOLITHOGRAPHY ADDITIVE MANUFACTURING USING THE RESPONSE SURFACE METHOD - Dicks, James Anthony; Hoosain, Mohammed Imran; Mbele, Onkhopotse (The South African Journal of Industrial Engineering, 2024)
Masked stereolithography is an effective and economical additive manufacturing technology that is suitable to fabricate objects for engineering applications. As such, parametric optimisation to attain good mechanical properties is of value in order to realise its full potential. A multi-objective optimisation of the printing parameters of masked stereolithography 3D printing for mechanical properties was performed using central composite design for response surface method analysis. The developed response surfaces were used to perform numerical optimisation to establish appropriate printing parameters, which were validated against experimental results and compared with bulk polymer specimen mechanical properties. Here, an optimised layer cure time of 3.8 s, a layer height of 50 μm, and a post-curing time of 13.5 min resulted in mechanical properties closely predicted by the model and near to bulk polymer specimen properties. Last, the optimisation results were related to a Jacobs working curve, which established that layer cure times beyond that determined by the Jacobs working curve were favoured.